Bentuk Tindak Tutur Berdasarkan Konteks Film â€œManusia Setengah Salmonâ€ Babak I - Langi, Fienny (Universitas Sam Ratulangi, 2017)
Speech act is a speech in which there is action. By saying something, the speakers also do something. By telling a speech, the speaker has a goal to be achieved from the partner that people speak with. To translate what was said by the addressees is good to know the context in question. Context is very important in understanding and interpreting the discourse. Context is something that we cannot ignore it, when people are trying to get the real meaning of information is heard or read. Context can affect a person's speech and is important in communicating. In communicating, use appropriate communication media. Film is also a medium to communicate an idea or the idea of the creator to a broad audience. Film creators can pour suggestion, innuendo, or other information in accordance with the events that are usually being much talked about. In this paper, the author selects the object data is a movie called